Aortic Thrombosis Associated with Three Types of COVID-19 Vaccine - Jose Maria Pereira de Godoy; Fernando Reis Neto; Gabriela Leopoldino da Silva; Henrique Amorim Santos; Henrique Jose Pereira de Godoy (Case Reports in Surgery)
Aortic thrombosis has been studied little in patients with COVID-19 and an association has recently been reported with the vaccine for this disease. The aim of the present study is to report five cases of aortic thrombosis at our institution within a three-month period associated with the COVID-19 vaccine. Five cases of aortic thrombosis were evaluated—three women and two men aged 29, 49, 51, 60, and 79 years. Four thrombi involved the thoracic aortic and one involved the abdominal aorta, with embolisms found in the kidneys, spleen, liver, upper limbs, and lower limbs. Embolectomy was performed on the limbs, and anticoagulant therapy was performed for the abdominal arteries. The patients recovered well and anticoagulant therapy was maintained. Aortic thrombosis is uncommon but was associated with the AstraZeneca vaccine in this case series.